2014
DOI: 10.1089/apc.2014.0121
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination in HIV-Infected Adults

Abstract: Vaccines are critical components for protecting HIV-infected adults from an increasing number of preventable diseases. However, missed opportunities for vaccination among HIV-infected persons persist, likely due to concerns regarding the safety and efficacy of vaccines, as well as the changing nature of vaccine guidelines. In addition, the optimal timing of vaccination among HIV-infected adults in regards to HIV stage and receipt of antiretroviral therapy remain important questions. This article provides a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 113 publications
(169 reference statements)
0
53
0
11
Order By: Relevance
“…Gli studi condotti al riguardo sono pochi e peraltro poco consistenti (17). Supposto che l'immuno-ricostituzione indotta dalla terapia aumenti l'efficacia del preparato vaccinale somministrato (20), la scelta di attendere una conta adeguata di linfociti T CD4 e una bassa viremia sembrerebbe quella più opportuna; d'altro canto, ogni vaccinazione procrastinata rappresenta una mancata opportunità di immunizzazione, per cui ci si assume il rischio di una potenziale esposizione o di perdita del paziente al follow-up (21,22). Un altro territorio di incertezza è quello relativo alla sicurezza dei preparati vaccinali.…”
Section: La Vaccinazione Nel Paziente Con Infezione Da Hivunclassified
See 2 more Smart Citations
“…Gli studi condotti al riguardo sono pochi e peraltro poco consistenti (17). Supposto che l'immuno-ricostituzione indotta dalla terapia aumenti l'efficacia del preparato vaccinale somministrato (20), la scelta di attendere una conta adeguata di linfociti T CD4 e una bassa viremia sembrerebbe quella più opportuna; d'altro canto, ogni vaccinazione procrastinata rappresenta una mancata opportunità di immunizzazione, per cui ci si assume il rischio di una potenziale esposizione o di perdita del paziente al follow-up (21,22). Un altro territorio di incertezza è quello relativo alla sicurezza dei preparati vaccinali.…”
Section: La Vaccinazione Nel Paziente Con Infezione Da Hivunclassified
“…Un altro territorio di incertezza è quello relativo alla sicurezza dei preparati vaccinali. Sulla base dei dati pubblicati in letteratura, il profilo di sicurezza dei vaccini inattivati nei soggetti con infezione da HIV sembra essere sovrapponibile a quello della popolazione sana (22). Benché non siano stati condotti studi con una potenza sufficiente per rilevare la comparsa di eventi avversi rari, i dati post-marketing non suggeriscono di porre particolare attenzione a questa categoria di soggetti (22).…”
Section: La Vaccinazione Nel Paziente Con Infezione Da Hivunclassified
See 1 more Smart Citation
“…A recent review concluded that vaccines in HIV patients generally trigger poorer immune responses than in healthy volunteers [105]. Therefore it seems likely that the protective effect of a 4CMenB vaccination would be weaker and of shorter duration for this risk group than for healthy persons.…”
Section: Potential Efficacy Of a 4cmenb Vaccination In Hiv Infectionmentioning
confidence: 99%
“…Оскільки дифтерія та правець не мають особливого зв'язку з ВІЛ-інфекцією, то рекомендації з вакцинації цієї групи в основному збігаються з рекомендаціями для загального населення [8], але, зважаючи на можли-вості відмінностей в імунному статусі ЛЖВ дорослого віку, це є дискусійним питанням.…”
unclassified